2023
DOI: 10.3390/ijms24043446
|View full text |Cite
|
Sign up to set email alerts
|

Lanthanides-Substituted Hydroxyapatite for Biomedical Applications

Abstract: Lately, there has been an increasing demand for materials that could improve tissue regenerative therapies and provide antimicrobial effects. Similarly, there is a growing need to develop or modify biomaterials for the diagnosis and treatment of different pathologies. In this scenario, hydroxyapatite (HAp) appears as a bioceramic with extended functionalities. Nevertheless, there are certain disadvantages related to the mechanical properties and lack of antimicrobial capacity. To circumvent them, the doping of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 164 publications
0
2
0
Order By: Relevance
“…Therefore, it is very crucial to reduce inflammation in proper timing and enhance the ability of cells that reside in the tooth pulp to heal itself. Studies showed nHAp has some shortcomings, such as its lowered antibacterial and anti-inflammatory properties 38 . To produce nHAp as a green synthesize to have the ability of drug delivery and anti-inflammatory ability and bone formation, we decided to assess the properties of nHAp synthesized with Elaeagnus angustifolia L. extract as drug delivery platforms for metronidazole to treat pulpitis.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is very crucial to reduce inflammation in proper timing and enhance the ability of cells that reside in the tooth pulp to heal itself. Studies showed nHAp has some shortcomings, such as its lowered antibacterial and anti-inflammatory properties 38 . To produce nHAp as a green synthesize to have the ability of drug delivery and anti-inflammatory ability and bone formation, we decided to assess the properties of nHAp synthesized with Elaeagnus angustifolia L. extract as drug delivery platforms for metronidazole to treat pulpitis.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, some HA dopants can substitute similar roles as growth factors. Due to these improved properties, doped HA nanoparticles are considered in biomedical applications as antimicrobial agents, bioimaging probes, drug carriers, and theragnostic agents [115]. In this regard, Jian et al reported that the use of HA in drug delivery systems is highly encouraged due to its excellent adsorption capacity and biocompatibility.…”
Section: Comparison Of Non-doped and Doped Hydroxyapatite: Properties...mentioning
confidence: 99%
“…Apatite-type structured compounds have been extensively studied for their potential in luminescence applications, thanks to their compositionally flexible network structure, which allows for easy substitution of various ions in cationic or anionic sites. 3,[11][12][13] In this study, we designed apatite-type compounds with chemical formula Ca 10 (PO 4 ) 5 (CO 3 )Cl 2 doped with Sm 3+ ions to create redemitting phosphors. It is established that Cl À ions significantly boost the emission efficiency of lanthanide ions, in contrast to OH À ions, which can lead to strong non-radiative energy migration.…”
Section: Introductionmentioning
confidence: 99%
“…Nanoparticles doped with these ions can be potentially used as biolabels due to advantages such as high photostability, narrow emission lines, long lifetimes, and low cytotoxicity. [7][8][9][10][11] It is well known that the host material significantly affects the performance of phosphors containing lanthanide ions. Apatite-type structured compounds have been extensively studied for their potential in luminescence applications, thanks to their compositionally flexible network structure, which allows for easy substitution of various ions in cationic or anionic sites.…”
Section: Introductionmentioning
confidence: 99%